Flexible composite mechanical energy harvester from a ferroelectric organoamino phosphonium salt - Vijayakanth, Thangavel; Srivastava, Anant Kumar; Ram, Farsa; Kulkarni, Priyangi; Shanmuganathan, Kadhiravan; Praveenkumar, Balu; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2018)
A new binary organic salt diphenyl diisopropylamino phosphonium hexaflurophosphate (DPDPPF6) was shown to exhibit a good ferroelectric response and employed for mechanical energy harvesting application. The phosphonium salt crystallizes in the monoclinic noncentrosymmetric space group Cc and exhibits an H-bonded 1D chain structure due to N-HF interactions. Ferroelectric measurements on the single crystals of DPDPPF6 gave a well-saturated rectangular hysteresis loop with a remnant (P-r) polarization value of 6Ccm(-2). Further, composite devices based on polydimethylsiloxane (PDMS) films for various weight percentages (3, 5, 7, 10 and 20wt%) of DPDPPF6 were prepared and examined for power generation by using an impact test setup. A maximum output peak-to-peak voltage (V-PP) of 8.5V and an output peak-to-peak current (I-PP) of 0.5A was obtained for the non-poled composite film with 10wt% of DPDPPF6. These results show the efficacy of organic ferroelectric substances as potential micropower generators.
Keywords: binary phosphonium salts; energy conversion; ferroelectricity; hydrogen bonding; polymer composites

All-organic composites of ferro- and piezoelectric phosphonium salts for mechanical energy harvesting application - Vijayakanth, Thangavel; Ram, Farsa; Praveenkumar, Balu; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Chemistry of Materials, 2019)
Molecular ferroelectrics owing to their lightweight, flexibility, and phase stability are drawing attention in the fields of flexible electronics, optical devices, and energy materials. In this paper, we report a series of binary organoamino phosphonium salts containing triphenyl isopropylaminophosphonium (TPAP), diphenyl diisopropylaminophosphonium (DPDP), phenyl triisopropylaminophosphonium (PTAP), and tetraisopropylaminophosphonium (TIAP) cations supported by lower symmetric tetrahedral BF4-, ClO4-, and IO4- anions. The P-E hysteresis loop measurements on these polar organic salts gave high remnant polarization (P-r) values of 35.36, 21.83, and 21.12 mu C cm(-2) for the DPDP center dot BF4, DPDP center dot ClO4, and DPDP center dot IO4 salts, respectively, having 1D hydrogen-bonded chain structures built from strong N-H center dot center dot center dot X (X = F or 0) interactions. For the first time, highly flexible composite devices have been prepared for the piezoelectric salts TPAP center dot BF4, DPDP center dot BF4, and TIAR center dot BF4 using thermoplastic polyurethane (TPU) as the matrix. The observed maximum peak-to-peak output voltages (V-pp) for the 10 wt % composite devices of TPAP center dot BF4/TPU, DPDP center dot BF4/TPU, and TIAP center dot BF4/TPU are found to be 7.37, 8.95, and 4.75 V, respectively. These composite devices exhibit excellent durability, cycling stability, and viscoelastic properties. They also show the capacitor charging capabilities reaching their maximum charging points within 60 s.

Nanocellulose reinforced flexible composite nanogenerators with enhanced vibrational energy harvesting and sensing properties - Ram, Farsa; Gudadhe, Aniket; Vijayakanth, Thangavel; Aherrao, Swapnil; Borkar, Vivek; Boomishankar, Ramamoorthy; Shanmuganathan, Kadhiravan (2020)
We report here enhanced vibration and pressure sensing properties of nanocellulose reinforced flexible composite piezoelectric nanogenerators (PENGs). Surface fluorinated nanocellulose crystals (FNC) were incorporated into poly(vinylidene fluoride) (PVDF) and electrospun into composite nanofibers. Incorporation of only 2 wt % FNC in PVDF resulted in a significant enhancement in pressure sensitivity with a very low detectable pressure limit of 10 Pa and a sensitivity of up to 18 mV/kPa. The composite PENGs also demonstrated very high sensitivity for forced continuous vibrations. 2FNC/PVDF composites resulted in an order of magnitude higher voltage response over neat PVDF for a given strain. When PENGs were mounted on a vacuum pump for transduction of mechanical vibrations into electrical energy, 2FNC/PVDF composite devices manifested similar to 3.8 times enhanced voltage output over neat PVDF and faster charging of a capacitor. The enhanced piezoelectric properties of PVDF/FNC nanocomposites could be attributed to the tailored interface between PVDF and nanocellulose and enhanced polarizability.
Keywords: Composite; Nanofiber; piezoelectric; pressure; Sensor; vibration

Piezoelectric energy harvesting from a ferroelectric hybrid salt [Ph3MeP](4)[Ni(NCS)(6)] embedded in a polymer matrix - Vijayakanth, Thangavel; Ram, Farsa; Praveenkumar, Balu; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2020)
Organic-inorganic hybrid ferroelectrics are an exciting class of molecular materials with promising applications in the area of energy and electronics. The synthesis, ferroelectric and piezoelectric energy harvesting behavior of a 3d metal ion-containing A(4)BX(6) type organic-inorganic hybrid salt [Ph3MeP](4)[Ni(NCS)(6)] (1) is now presented. P-E hysteresis loop studies on 1 show a remnant ferroelectric polarization value of 18.71 mu C cm(-2), at room temperature. Composite thermoplastic polyurethane (TPU) devices with 5, 10, 15 and 20 wt % compositions of 1 were prepared and employed for piezoelectric energy harvesting studies. A maximum output voltage of 19.29 V and a calculated power density value of 2.51 mW cm(-3) were observed for the 15 wt % 1-TPU device. The capacitor charging experiments on the 15 wt % 1-TPU composite device shows an excellent energy storage performance with the highest stored energies and measured charges of 198.8 mu J and 600 mu C, respectively.
Keywords: energy conversion; mechanical properties; non-covalent interactions; organic-inorganic hybrid composites; Phosphorus

Ferroelectric aminophosphonium cyanoferrate with a large electrostrictive coefficient as a piezoelectric nanogenerator - Vijayakanth, Thangavel; Sahoo, Supriya; Kothavade, Premkumar; Sharma, Vijay Bhan; Kabra, Dinesh; Zareba, Jan K. K.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2023)
Hybrid materials possessing piezo- and ferroelectric properties emerge as excellent alternatives to conventional piezoceramics due to their merits of facile synthesis, lightweight nature, ease of fabrication and mechanical flexibility. Inspired by the structural stability of aminophosphonium compounds, here we report the first A(3)BX(6) type cyanometallate [Ph-2((PrNH)-Pr-i)(2)P](3)[Fe(CN)(6)] (1), which shows a ferroelectric saturation polarization (P-s) of 3.71 mu C cm(-2). Compound 1 exhibits a high electrostrictive coefficient (Q(33)) of 0.73 m(4) C-2, far exceeding those of piezoceramics (0.034-0.096 m(4) C-2). Piezoresponse force microscopy (PFM) analysis demonstrates the polarization switching and domain structure of 1 further confirming its ferroelectric nature. Furthermore, thermoplastic polyurethane (TPU) polymer composite films of 1 were prepared and employed as piezoelectric nanogenerators. Notably, the 15 wt % 1-TPU device gave a maximum output voltage of 13.57 V and a power density of 6.03 mu W cm(-2).
Keywords: Cyanometallates; energy conversion; H-bonding; hybrid composites; Phosphorus